Customer Co-Creation Throughout the Product Life Cycle - Orcik, Anja; Tekic, Zeljko; Anisic, Zoran (International Journal of Industrial Engineering and Management, 2013)
To sustain their competitive advantage, companies rely more and more on customers’ knowledge and experiences in product innovation processes. Considering that for radical innovations a distance from current market needs is crucial, customers arenot in great amount involved in the development of products that represent breakthroughs on the market. However, customers’ knowledge and experienceis very importantfor the incremental product improvements. Co-creation can be seen as a powerful engine for innovation. This paper focuses on giving the answer to the research question –is it possible to map co-creation processes throughout the product life cycle? By means of a literature review, the authors try to provide the understanding of this relation and offer the distinction ofthree co-creation levels(breakthrough level, high co-creation and low co-creation level) throughout the life cycle of aproduct. Article history: Received (23 December 2012); Revised (11January 2013); Accepted (14February 2013)